KONFLIK PERAN, AMBIGUITAS PERAN, MOTIVASI, DAN KOMPETENSI, BAGAIMANA PENGARUHNYA TERHADAP INDEPENDENSI AUDITOR INTERNAL PEMERINTAH: ROLE CONFLICT, ROLE AMBIGUITY, MOTIVATION, AND COMPETENCE, HOW IT INFLUENCES THE INDEPENDENCE OF GOVERNMENT INTERNAL AUDITORS - Malvin Alianro Depari; Choirul Anwar; Hafifah Nasution (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to examine the effect of role conflict, role ambiguity, motivation, and competence on the independence of internal auditors. This study makes internal auditors who work at the Inspectorate General of the Ministry of Education, Culture, Research and Technology as the population. The type of data in this study is primary data, with data acquisition techniques through questionnaires. The total population in this study amounted to 284 and the sample used in this study was 76 respondents. The questionnaires distributed totaled 86 items and the questionnaires that were filled in totaled 76 items. The questionnaire data were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) results of this study indicate that role conflict, role ambiguity, and motivation have no effect on the independence of the government's internal auditors. Meanwhile, competence is proven to have a positive effect on the independence of the government's internal auditors. This study hopes that government internal auditors can continue to improve their competence in order to better understand their duties and roles at work which will also have an impact on increasing work motivation and independence of internal auditors.